Analisis Pemanfaatan Energi Biogas Dari Campuran Limbah Kotoran Sapi Dan Kulit Durian Sebagai Energi Alternatif - Doddy Suanggana (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2020)
The continuous use of fossil energy as an energy source will have an impact on the environment and the availability of fossil energy sources. As a precautionary measure due to the impact of the use of fossil energy, the use of renewable energy as an alternative energy to substitute for fossil energy is decreasing. One of the ways to use renewable energy is biogas technology. This biogas uses waste or underutilized animal waste as an energy source. This study aims to determine the utilization of biogas energy production from a mixture of cow dung and durian peel. The production of biogas energy will be used for gas stoves and rice cookers. The research method uses quantitative methods, starting from making biogas technology tools, collecting biogas raw materials and collecting data and biogas utilization testing. Variations of a mixture of cow dung and durian peel 50:50; 70:30; 80:20. From the test results, the 70:30 variation has the best biogas production compared to the 50:50 and 80:20 variations. The maximum pressure is obtained on the 15th day with pressure 0.15 Bar with the gas volume 0.088 m3 and the volume of gas produced for 30 days is 1.2605 m3. The color of the flame from the biogas energy is bluish and there are reddish sparks and the stove has a long flame for 9 minutes 49 seconds to boil 1000 ml of water. The time needed to cook 100 grams of rice in the rice cooker for 7 minutes 30 seconds.